The Influence of Leadership Style on Employee Performance and Employee Work Motivation at Dr Tadjuddin Chalid Hospital Makassar - Linda Yohanis; Djabir Hamzah; Muhammad Idrus Taba (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2021)
This study aims to analyze and determine the effect of leadership style on employee performance and employee motivation at DR Tadjuddin Chalid Hospital Makassar. The research uses a quantitative approach. The population in this study were all employees of DR Tadjuddin Chalid Hospital Makassar, amounting to 548 people with a total sample of 84 respondents. Data was collected using a questionnaire. Data analysis used descriptive statistics and path analysis with PLS 3.0 to analyze the direct and indirect effects on employee performance at DR Tadjuddin Chalid Hospital Makassar. The results of this study indicate that partially leadership style and work motivation have a positive and significant effect on employee performance. While work motivation has a positive and significant effect on employee performance. Leadership style has a positive and significant effect on employee performance through work motivation as a mediating or intervening variable. This means that leadership style has a significant direct and indirect influence on employee performance at DR Tadjuddin Chalid Hospital Makassar.